2015
DOI: 10.1111/apha.12624
|View full text |Cite
|
Sign up to set email alerts
|

The change in motor unit firing rates at de‐recruitment relative to recruitment is correlated with type I myosin heavy chain isoform content of the vastus lateralis in vivo

Abstract: The majority of the motoneuron pool had greater FRDEREC than FRREC , however, individuals with higher type I %MHC had a greater propensity to have MUs with FRREC > FRDEREC as indicated by the slope values. Overall, the contractile properties of the muscle (MHC) could partially explain the differences in MU firing rates at de-recruitment relative to recruitment. Thus, suggesting the fatigability of the muscle influences the alterations in MU firing rates from recruitment to de-recruitment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…For all isometric trapezoid muscle actions, the torque was increased at 10% MVC/s to the desired torque level, where it was held during 12-seconds plateau and then decreased to baseline at a rate of 10% MVC/s. 41,[52][53][54] Therefore, the duration of each contraction lasted 20 seconds. The 40% MVC was chosen over higher-intensity contractions (ie 70% MVC) as the EMG decomposition method yields a high number of MUs (>23) with similar RT ranges (8-31% MVC) across subjects 10,53 unlike for a 70% MVC.…”
Section: Isometric Strength Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…For all isometric trapezoid muscle actions, the torque was increased at 10% MVC/s to the desired torque level, where it was held during 12-seconds plateau and then decreased to baseline at a rate of 10% MVC/s. 41,[52][53][54] Therefore, the duration of each contraction lasted 20 seconds. The 40% MVC was chosen over higher-intensity contractions (ie 70% MVC) as the EMG decomposition method yields a high number of MUs (>23) with similar RT ranges (8-31% MVC) across subjects 10,53 unlike for a 70% MVC.…”
Section: Isometric Strength Testingmentioning
confidence: 99%
“…10 In addition, it would be expected that a large percentage (~65%) of total MUs would be activated during the 40% MVC 47,48 and, thus, still provide valuable insight on characteristics of the MU pool via linear regressions. 41,52,54 Furthermore, it has been reported type I fibres in humans can contain fast myosin 49,50 and, thus, type II MHC is not limited to higherthreshold MUs. Three to five minutes of rest was given between each muscle action.…”
Section: Isometric Strength Testingmentioning
confidence: 99%
“…Given the MMG values at the failure point, it is possible that the degree of impairment in force twitch mechanics were similar at task failure, though this is speculative as this study did not directly measure evoked twitch responses or intramuscular metabolite concentrations. In addition, the curvilinear response patterns observed in this study may be explained by unique fatigue-based motor control strategies that result from different expressions of the myosin heavy chain isoform within the contributing motor units (Contessa et al 2016;Herda et al 2016;Trevino et al 2016). This explanation is supported by studies that have observed smaller absolute values and patterns of change for MMG amplitude and MNF for individuals with larger proportions of the type 1 myosin heavy chain isoform (Orizio and Veicsteinas 1992;Beck et al 2007b;Trevino et al 2016).…”
Section: Discussionmentioning
confidence: 83%
“…; Herda et al. ). Recent observations show that task failure corresponds with a specific level of intramuscular metabolic perturbation during single‐joint and whole‐body exercise (Burnley et al.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation